Functional Groups Mask Inter- and Intraspecific Variation in Water Use Strategies in a Seasonally Dry Tropical Forest - Adams, Rachel E.; West, Jason B. (Frontiers in Water, 2022)
Across the karst landscape of Quintana Roo, Mexico, plant access to nutrients and water appears limited by generally shallow soil. However, underlying this surface are heterogenous pockets in bedrock and deeper, stable groundwater, suggesting the potential for specialization by species in accessing soil resources. If species differentially access rock resources, divisions by functional groups may also be expected. In this study, shallow caves provided an opportunity to assess resource use strategies by direct, species-specific root observations coupled with traditional above ground measurements. Utilizing stable isotopes from stems and leaves (18O and 13C), we investigated water access and water use efficiency of trees during the dry season to uncover relationships between rooting habit, tree size, and pre-determined functional groups based on leaf habit and wood density. Functional group membership did not predict measured stable isotope ratios, indicating that functional groups were poor predictors of resource use. We did find evidence for deep water use by select species and larger individuals. Interestingly, as trees became larger, δ13C increased to a threshold but then declined, suggesting increasing vulnerability to water limitation as trees increase in size, consistent with other seasonally dry tropical forests. Our work demonstrates that, although shallow soils likely drive strong resource limitations, co-occurring trees in karst ecosystems employ diverse resource acquisition strategies, suggesting important consequences for community composition and ecosystem function in the face of environmental change.